Breast cancer screening coverage is severely reduced among women who reside in segregated areas: a cross-sectional investigation in Hungary - Odeh, Aseel; Feras, Kasabji; Vincze, Ferenc; Lakatos, Kinga; Pálinkás, Anita; Kőrösi, László; Ulicska, László; Kósa, Karolina; Sándor, János (Frontiers in Public Health, 2025)
BackgroundThis study investigated disparities in breast cancer screening participation between living in residential segregations (SAs, segregated areas defined by clustering of low levels of income and education) and in non-segregated, complementary areas (CAs) of Hungary.MethodsIn a nationwide cross-sectional study, data from 2019 were obtained from the National Health Insurance Fund (NHIF). In accordance with the Hungarian recommendation, the target group was composed of women aged 45–65, and screening participation was evaluated as appropriate if the women participated in mammography within 2 years. Standardized participation ratios (sPRs) were calculated for each SA and CA. These ratios were adjusted for age and eligibility for exemption certificates. The calculations were done for each general medical practice (GMP) serving a population with at least one SA, as well as for the whole country. The level of inequality was quantified by the relative standardized participation ratio (rsPR) by comparing sPR in the segregated versus non-segregated areas.ResultsThe study identified 11,581 observed breast cancer screening cases in SAs, compared with 417,891 in CAs, with target populations of 45,185 in SAs and 984,198 in CAs. In general, crude participation rates were significantly lower in SAs (25.6%) than in CAs (42.5%), with a rsPR of 0.62 (95% CI: 0.61–0.63). The impact of segregation on national screening coverage was negligible (population attributable risk: −1.2%). The GMP-level rsPR varied widely with a median of 0.653 and interquartile range (IQR) of 0.464–0.867. Notably, 15.6% of the GMPs had significantly reduced rsPR.ConclusionThis study demonstrated that breast cancer screening coverage is considerably lower among women living in SAs than in those living in non-segregated areas. GMPs showed substantial variability with respect to segregation related inequality. There was a remarkable proportion of GMPs without local inequality. The impact of segregation on national breast cancer screening participation was negligible. According to our observations, the segregation-specific indicators should be included in screening monitoring, and its results should be feedback to local authorities and stakeholders in order to identify and address local problems of screening organization to reduce inequalities.